Pragmatism, Need For Comfort And Need For Acceptance -Psychological Traits For Successful Entrepreneurship In Portugal - Galvão, Ana; Pinheiro, Marco (Journal of Tourism, Sustainability and Well-being, 2017)
The purpose of this study was to revisit the inventory developed by Galvão and Pinheiro (2016), measuring seven psychological traits common to business owners, and to propose an inventory that could improve the measuring of psychological traits of Portuguese business owners. The 26 items inventory was used on two samples. Sample 1, included 229 individuals (33.2% business owners) and Sample 2, used to cross-validate findings, included 257 individuals (44.0% business owners). Correlational statistical tests and a Principal Component Analysis were carried out, resulting in items loading to 3 components. The loading items were presented to 17 business owners to validate the trait they most associated to each question, resulting in a fit to 16 items also identified by the authors as having theoretical foundations. Structural Equation Modelling was performed showing good fits for both sample 2 (RMSEA=0.052; TLI=0.942; CFI=0.951) as sample 1 (RMSEA=0.036; TLI=0.966; CFI=0.971). With this study we were able to create the Portuguese Entrepreneurial Psychological Traits Inventory (PEPTI), an inventory that measures psychological traits that are significantly higher in business owners and that is adapted to Portuguese culture and that overcame the issues pointed out by Galvão and Pinheiro (2016) in their study.